Modified mesoporous silica supported nickel-molybdenum bimetallic catalyst and preparation method and application thereof

By modifying the mesoporous silica-supported nickel-molybdenum bimetallic catalyst, the problem of insufficient yield and selectivity of alcohol products in the hydrodeoxygenation conversion reaction of biomass-derived biooils is solved, and efficient cycloalkanol production is achieved.

CN119657157APending Publication Date: 2025-03-21YULIN UNIV +1
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411798170.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-09
Publication Date
2025-03-21

AI Technical Summary

Technical Problem

In the hydrodeoxygenation conversion reaction of biomass-derived biooils, the traditional molybdenum-based and nickel-based catalysts have weak hydrogen dissociation ability, resulting in low yield and poor selectivity of alcohol products.

Method used

The catalyst was prepared by co-precipitation method and calcining steps to improve the stability and activity of the catalyst.

Benefits of technology

The yield and selectivity of alcohol products was significantly improved, especially in the hydrodeoxygenation conversion reaction of biomass-derived biooils, and higher cycloalkanol yield and selectivity were obtained.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119657157A_ABST
    Figure CN119657157A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of catalytic materials, in particular to a catalyst and a preparation method and application thereof. The invention provides a catalyst. The catalyst comprises organosilane modified mesoporous silica and nickel-molybdenum bimetallic loaded in the organosilane modified mesoporous silica. Nickel in the catalyst can promote hydrogen activation and hydrogenation, and molybdenum plays a role in catalytic cracking reaction. On the catalyst, the synergistic effect generated by combination of bimetal and acidic sites is more beneficial to efficient HDO reaction (catalytic hydrodeoxygenation reaction). The result of the embodiment shows that when the conversion rate of the model compound guaiacol is 100%, the highest selectivity of the obtained product naphthenic alcohol can reach 50.1%; when the catalyst is applied to the hydrodeoxygenation conversion reaction process of biomass alcoholysis derivative oil, the yield of naphthenic alcohol is greatly increased, and the relative content is increased from 3.5% to 49.8%.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of catalytic materials, and in particular to a modified mesoporous silica-supported nickel-molybdenum bimetallic catalyst and a preparation method and application thereof. Background Art

[0002] Biomass is a sustainable and renewable resource that can be degraded into liquid bio-oil and a variety of valuable chemicals. Lignin is considered to be a byproduct of many biomass refining processes and is the largest renewable resource of aromatic structural units in nature. Its conversion and utilization has become a research hotspot. In particular, converting lignin in biomass into high-value-added alcohol compounds is of great significance for promoting energy substitution and greening of chemical raw materials.

[0003] Due to the high degree of condensation of lignin and its difficulty in depolymerization, it has always been a challenging problem to efficiently convert lignin-derived bio-oil into alcohol chemicals by saturated hydrogenated aromatic rings without deoxygenation. The traditional molybdenum-based and nickel-based catalysts have weak hydrogen dissociation ability, which will result in low yield and poor selectivity of alcohol products obtained in the hydrodeoxygenation reaction of biomass-derived bio-oil. In order to meet the growing resource needs, it is urgent to design a bimetallic catalyst with excellent performance to accurately control the conversion of active hydrogen species, thereby improving the yield and selectivity of alcohol products. Summary of the invention

[0004] The purpose of the present invention is to provide a modified mesoporous silica-supported nickel-molybdenum bimetallic catalyst and its preparation method and application. The modified mesoporous silica-supported nickel-molybdenum bimetallic catalyst is applied to the hydrodeoxygenation conversion reaction of Salix psammophila-derived bio-oil, which can effectively improve the yield and selectivity of alcohol products.

[0005] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:

[0006] The invention provides a catalyst, comprising organosilane-modified mesoporous silica and a nickel-molybdenum bimetal supported on the organosilane-modified mesoporous silica.

[0007] Preferably, the loading amount of the nickel-molybdenum bimetal in the organosilane-modified mesoporous silica is 10 wt % to 40 wt %.

[0008] Preferably, the mass ratio of nickel to molybdenum in the nickel-molybdenum bimetal is 1:(1-4).

[0009] The present invention also provides a method for preparing the catalyst described in the above technical solution, comprising the following steps:

[0010] After mixing organosilane-modified mesoporous silica, soluble molybdenum salt, soluble nickel salt and water, ammonia water is added dropwise to perform a coprecipitation reaction to obtain a catalyst precursor;

[0011] The catalyst precursor is calcined in a reducing atmosphere to obtain the catalyst.

[0012] Preferably, the soluble molybdenum salt is ammonium molybdate tetrahydrate and / or ammonium heptamolybdate;

[0013] The soluble nickel salt is nickel nitrate hexahydrate and / or nickel sulfate heptahydrate;

[0014] The mass concentration of the ammonia water is 25-28%.

[0015] Preferably, the mass ratio of the organosilane-modified mesoporous silica to the soluble molybdenum salt is 1:(0.5-4);

[0016] The mass ratio of the organosilane-modified mesoporous silica to the soluble nickel salt is 1:(0.3-1.5);

[0017] The usage ratio of the organosilane-modified mesoporous silica and ammonia water is 1 g: (1-5) mL;

[0018] The usage ratio of the organosilane-modified mesoporous silica to water is 1 g: (10-60) mL.

[0019] Preferably, the calcination temperature is 400-550° C. and the calcination time is 4-8 hours.

[0020] Preferably, the method for preparing the organosilane-modified mesoporous silica comprises the following steps:

[0021] The silicon source aqueous solution and the methanol solution of the organosilane are mixed, and then refluxed, stirred, washed and dried in sequence to obtain the organosilane-modified mesoporous silica.

[0022] Preferably, the silicon source in the silicon source aqueous solution includes silicon dioxide and / or sodium silicate;

[0023] The organosilane in the methanol solution of organosilane includes dimethyloctadecyl[3-trimethoxysilylpropyl]ammonium chloride and / or dimethyloctadecyl[3-ethoxysilylpropyl]ammonium chloride.

[0024] The present invention also provides the use of the catalyst described in the above technical solution or the catalyst prepared by the preparation method described in the above technical solution in the hydrodeoxygenation conversion reaction of biomass-derived bio-oil.

[0025] The present invention provides a catalyst, comprising organosilane-modified mesoporous silica and a nickel-molybdenum bimetal supported on the organosilane-modified mesoporous silica. Compared with unmodified silica, the mesoporous silica modified by organosilane in the catalyst of the present invention is more conducive to the contact between the catalyst and the substrate, and improves the stability of the catalyst; the nickel in the catalyst of the present invention can promote hydrogen activation and hydrogenation, while the molybdenum plays a role in breaking the CO bridge bond in the hydrodeoxygenation. On the catalyst, the synergistic effect generated by the combination of the bimetal and the acidic sites on the carrier can improve the electron transfer efficiency and the hydrodeoxygenation activity of the catalyst, which is more conducive to efficient HDO reaction (catalytic hydrodeoxygenation reaction). According to the results of the embodiment, the catalyst is used in the hydrodeoxygenation reaction of the model compound guaiacol to verify the catalytic activity of the hydrodeoxygenation conversion reaction of bio-derived bio-oil, and a higher yield of cycloalkanol is obtained; it is applied to the hydrodeoxygenation conversion reaction process of the derivative oil of biomass hydrocracking, and the yield and selectivity of cycloalkanol are significantly improved.

[0026] The present invention also provides a method for preparing the catalyst described in the above technical solution, comprising the following steps: mixing organosilane-modified mesoporous silica, soluble molybdenum salt, soluble nickel salt and water, dripping ammonia water, and performing a coprecipitation reaction to obtain a catalyst precursor; calcining the catalyst precursor in a reducing atmosphere to obtain the catalyst. The preparation method is simple, has a short production cycle, and is inexpensive; the dispersion degree of nickel and molybdenum is high, and there is no obvious agglomeration; the catalyst prepared by the coprecipitation method will become rough due to the deposition of nickel and molybdenum, the pore size becomes larger, and the hydrogenation capacity is enhanced, which is conducive to obtaining cycloalkanol from biomass-derived bio-oil in situ with high yield. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] Figure 1 The XRD diagram of the mesoporous silica and the catalyst described in Example 1;

[0028] Figure 2 The scanning electron microscope image and energy dispersion spectrum of the mesoporous silica described in Example 1 (a), the scanning electron microscope image and energy dispersion spectrum of the catalyst (b), and the element distribution map of the catalyst (c);

[0029] Figure 3 is an X-ray photoelectron spectroscopy (XPS) diagram of the catalyst described in Example 1;

[0030] Figure 4 The N2 adsorption-desorption curve and pore size distribution diagram of the mesoporous silica and the catalyst described in Example 1;

[0031] Figure 5 This is a comparison chart of the product components before and after hydrogenation of the light component described in Application Example 1. DETAILED DESCRIPTION

[0032] The invention provides a catalyst, comprising organosilane-modified mesoporous silica and a nickel-molybdenum bimetal supported on the organosilane-modified mesoporous silica.

[0033] In the present invention, the loading amount of the nickel-molybdenum bimetal in the mesoporous silica is preferably 10wt% to 40wt%, more preferably 20wt% to 30wt%. In an embodiment of the present invention, the loading amount of the nickel-molybdenum bimetal in the mesoporous silica can be 10wt%, 20wt%, 30wt% and 40wt%.

[0034] In the present invention, the mass ratio of nickel to molybdenum in the nickel-molybdenum bimetal is preferably 1:(1-4). In an embodiment of the present invention, the mass ratio of nickel to molybdenum can be 1:1.

[0035] In the present invention, the average pore size (APS) of the catalyst is preferably 13 to 15 nm. t ) is preferably 0.40 to 0.50 M 3 ·g -1 , where the mesopore volume (V mic ) is preferably 0.40 to 0.50 M 3 ·g -1 .

[0036] The present invention also provides a method for preparing the catalyst described in the above technical solution, comprising the following steps:

[0037] After mixing organosilane-modified mesoporous silica, soluble molybdenum salt, soluble nickel salt and water, ammonia water is added dropwise to perform a coprecipitation reaction to obtain a catalyst precursor;

[0038] The catalyst precursor is calcined in a reducing atmosphere to obtain the catalyst.

[0039] In the present invention, unless otherwise specified, all preparation raw materials are commercially available products well known to those skilled in the art.

[0040] The present invention mixes organosilane-modified mesoporous silica, soluble molybdenum salt, soluble nickel salt and water, then drips ammonia water to carry out a coprecipitation reaction to obtain a catalyst precursor.

[0041] In the present invention, the method for preparing the organosilane-modified mesoporous silica preferably comprises the following steps:

[0042] The silicon source aqueous solution and the methanol solution of the organosilane are mixed, and then refluxed, stirred, washed and dried in sequence to obtain the organosilane-modified mesoporous silica.

[0043] In the present invention, the silicon source in the silicon source aqueous solution preferably includes silicon dioxide and / or sodium silicate. When the silicon source is silicon dioxide and sodium silicate, the present invention does not have any special restrictions on the ratio of silicon dioxide and sodium silicate, and they can be mixed in any ratio. In an embodiment of the present invention, the silicon source can be silicon dioxide. In the present invention, the water in the silicon source aqueous solution is preferably deionized water.

[0044] In the present invention, the method for preparing the silicon source aqueous solution is preferably to mix the silicon source and water. In the present invention, the dosage ratio of the silicon source and water is preferably 1g: (10-30) mL, more preferably 1g: (15-25) mL. In an embodiment of the present invention, the dosage ratio of the silicon source and water can be 1g: 18mL. In the present invention, the mixing is preferably carried out under stirring conditions. The present invention does not have any special limitation on the stirring process, and the stirring process can be carried out using a process well known to those skilled in the art.

[0045] In the present invention, the organosilane in the methanol solution of the organosilane preferably includes dimethyl octadecyl [3-trimethoxysilyl propyl] ammonium chloride and / or dimethyl octadecyl [3-ethoxysilyl propyl] ammonium chloride. When the organosilane is dimethyl octadecyl [3-trimethoxysilyl propyl] ammonium chloride and dimethyl octadecyl [3-ethoxysilyl propyl] ammonium chloride, the present invention does not have any special restrictions on the ratio of the dimethyl octadecyl [3-trimethoxysilyl propyl] ammonium chloride and dimethyl octadecyl [3-ethoxysilyl propyl] ammonium chloride, and can be mixed in any ratio. In an embodiment of the present invention, the organosilane can be dimethyl octadecyl [3-trimethoxysilyl propyl] ammonium chloride.

[0046] In the present invention, the method for preparing the methanol solution of the organosilane is preferably to mix the organosilane and methanol. In the present invention, the mass ratio of the organosilane to methanol is preferably 1:(4-8), more preferably 1:(5-7). In an embodiment of the present invention, the mass ratio of the organosilane to methanol may be 1:7. In the present invention, the mixing is preferably carried out under conditions of vigorous stirring, and the rotation speed of the vigorous stirring is preferably 1300-1600rpm, more preferably 1400-1500rpm. In an embodiment of the present invention, the rotation speed of the vigorous stirring may be 1500rpm.

[0047] In the present invention, the mass ratio of the silicon source in the silicon source aqueous solution to the organosilane in the methanol solution of the organosilane is preferably 5:(1-4), more preferably 5:(1-3). In an embodiment of the present invention, the mass ratio of the silicon source to the organosilane may be 5:2.

[0048] In the present invention, the temperature of the reflux stirring is preferably 80-140°C, more preferably 90-130°C, and most preferably 100-120°C; the time is preferably 6-12h, more preferably 8-10h. The present invention does not have any special restrictions on the stirring process of the reflux stirring, and the process well known to those skilled in the art can be used. In an embodiment of the present invention, the temperature of the reflux stirring can be 100°C and the time can be 8h. In the present invention, the reflux process is a surface modification process, a hydrolysis process and a polycondensation process. Specific functional groups may be introduced in the surface modification process. These surface modification processes usually occur during the reflux process, and the modifier is connected to the surface of the silica by chemical bonding; the hydrolysis process is to use organic silane to hydrolyze under acidic or alkaline conditions to generate silicic acid and the corresponding alcohol; the polycondensation process is that the silicic acid molecules produced by hydrolysis will further undergo polycondensation to form Si-O-Si bonds to form a silica network structure.

[0049] In the present invention, the washing is preferably carried out with ethanol. The present invention does not have any special limitation on the washing process, and the washing process can be carried out by a process well known to those skilled in the art. In the present invention, the drying method is preferably vacuum drying; the vacuum drying temperature is preferably 80 to 130°C, more preferably 90 to 120°C, and most preferably 90 to 120°C; the vacuum drying time is preferably 10 to 26h, more preferably 11 to 25h, and most preferably 12 to 24h. In an embodiment of the present invention, the vacuum drying temperature can be 90°C and the time can be 16h.

[0050] In the present invention, the soluble molybdenum salt is preferably ammonium molybdate tetrahydrate and / or ammonium heptamolybdate, more preferably ammonium molybdate tetrahydrate; the soluble nickel salt is preferably nickel nitrate hexahydrate and / or nickel sulfate heptahydrate, more preferably nickel nitrate hexahydrate; the mass concentration of the ammonia water is preferably 25-28%. In an embodiment of the present invention, the mass concentration of the ammonia water can be 28%. In the present invention, the ammonia water will not destroy the crystal structure during the coprecipitation process, and secondly, it will avoid other ions being loaded on the metal while forming a good precipitate, thereby affecting the catalyst activity.

[0051] In the present invention, the mass ratio of the organosilane-modified mesoporous silica and the soluble molybdenum salt is preferably 1:(0.5-4), and more preferably 1:(1-3); the mass ratio of the organosilane-modified mesoporous silica and the soluble nickel salt is preferably 1:(0.3-1.5), and more preferably 1:(0.4-1.2); the dosage ratio of the organosilane-modified mesoporous silica and ammonia water is preferably 1g:(1-5)mL, and more preferably 1g:(2-3)mL; the dosage ratio of the organosilane-modified mesoporous silica and water is preferably 1g:(10-60)mL, and more preferably 1g:(40-60)mL. In an embodiment of the present invention, the dosage ratio of the mesoporous silica, soluble molybdenum salt, soluble nickel salt, water and ammonia water can be 1g:1.5g:0.6g:50mL:3mL, 1g:0.8g:0.3g:50mL:3mL, 1g:2.5g:0.9g:50mL:3mL or 1g:3.1g:1.4g:50mL:3mL.

[0052] The present invention does not have any special limitation on the mixing of the mesoporous silica, the soluble molybdenum salt, the soluble nickel salt and water, and the mixing can be carried out by a process well known to those skilled in the art.

[0053] In the present invention, the dropwise addition of the ammonia water is preferably carried out under stirring. The present invention does not have any special limitation on the stirring process, and the stirring process can be carried out using a process well known to those skilled in the art. In the present invention, the dropwise addition is preferably carried out drop by drop.

[0054] In the present invention, the pH value of the mixed solution obtained after the dropwise addition is preferably 8 to 10. In an embodiment of the present invention, the pH value of the mixed solution may be 9.

[0055] In the present invention, the coprecipitation reaction preferably occurs during the dropwise addition process, and after the dropwise addition is completed, further stirring is preferably performed to ensure that the coprecipitation reaction is complete.

[0056] After the dropwise addition is completed, the present invention also preferably includes centrifugal separation, washing and drying performed in sequence; in the present invention, the speed of the centrifugal separation is preferably 3000-5000rpm, more preferably 4000-5000rpm; the time is preferably 3-6min, more preferably 4-5min. In an embodiment of the present invention, the speed of the centrifugal separation can be 5000rpm, and the time can be 5min. The washing is preferably washed alternately with deionized water and anhydrous ethanol. In the present invention, the drying is preferably vacuum drying; the temperature of the vacuum drying is preferably 80-120°C, more preferably 90-110°C; the time is preferably 10-26h, more preferably 12-24h. In an embodiment of the present invention, the temperature of the vacuum drying can be 95°C, and the time can be 12h.

[0057] After obtaining the catalyst precursor, the present invention calcines the catalyst precursor in a reducing atmosphere to obtain the catalyst.

[0058] In the present invention, the reducing atmosphere is preferably a hydrogen atmosphere. The calcination temperature is preferably 400-550°C, more preferably 450-500°C; the calcination time is preferably 4-8h, more preferably 5-6h. In an embodiment of the present invention, the calcination temperature may be 500°C, and the calcination time may be 6h.

[0059] After the calcination is completed, the present invention also preferably includes passivation, and the passivation is preferably carried out in a nitrogen atmosphere; the flow rate of nitrogen in the nitrogen atmosphere is preferably 30 to 70 mL / min, more preferably 40 to 50 mL / min; the temperature of the passivation is preferably 10 to 40°C, more preferably 20 to 30°C; the time is preferably 0.5 to 2 hours, more preferably 1 to 1.5 hours. In an embodiment of the present invention, the flow rate of nitrogen can be 40 mL / min; the temperature can be 30°C; and the time can be 1 hour.

[0060] The present invention also provides the use of the catalyst described in the above technical solution or the catalyst prepared by the preparation method described in the above technical solution in the hydrodeoxygenation conversion reaction of biomass-derived bio-oil.

[0061] In the present invention, the application method preferably includes: mixing biomass-derived bio-oil, the catalyst described in the above technical solution and normal alkane substances, replacing air with nitrogen three times, and then pressurizing with hydrogen to 1-5 MPa for hydrodeoxygenation conversion reaction.

[0062] In the present invention, the biomass-derived bio-oil preferably includes one or more of methanolysis bio-oil, ethanolysis bio-oil and isopropanolysis bio-oil. When the biomass-derived bio-oil is two or more of the above specific selections, the present invention does not have any special restrictions on the ratio of the above specific substances, and they can be mixed in any ratio. Since the components in the above biomass-derived bio-oil include guaiacol and / or phenol, an application example of the catalyst described in the above technical solution catalyzing the hydrodeoxygenation conversion reaction of guaiacol (as a model compound) is also provided in the application verification experiment of the catalyst described in the above technical solution.

[0063] In the present invention, the normal alkane substance is preferably one or more of n-hexane, n-heptane, benzene and toluene. In the present invention, the function of the normal alkane substance is to fully dissolve the biomass-derived bio-oil and the catalyst, so that the biomass-derived bio-oil and the catalyst can be better contacted, thereby improving the catalytic activity.

[0064] In the present invention, the mass ratio of the biomass-derived bio-oil to the catalyst described in the above technical solution is preferably 1:(0.1-0.5), more preferably 1:(0.2-0.4). In the application example of the present invention, the mass ratio of the biomass-derived bio-oil to the catalyst described in the above technical solution can be 1:0.2.

[0065] In the present invention, the ratio of the biomass-derived bio-oil to n-hexane is preferably 15 g: (100-250) mL, more preferably 15 g: (150-200) mL. In the application example of the present invention, the ratio of the biomass-derived bio-oil to n-hexane can be 15 g: 200 mL.

[0066] In the present invention, the initial pressure of the hydrogen atmosphere is preferably 1-5 MPa, more preferably 4-5 MPa. In the application examples of the present invention, the initial pressure may be 1 MPa, 2 MPa, 3 MPa, 4 MPa or 5 MPa; the temperature of the hydrodeoxygenation conversion reaction is preferably 160-240°C, more preferably 180-200°C. In the application examples of the present invention, the temperature of the hydrodeoxygenation conversion reaction may be 160°C, 180°C, 200°C, 220°C or 240°C. In the present invention, the time of the hydrodeoxygenation conversion reaction is preferably 30-150 min, more preferably 60-120 min, and most preferably 90-120 min. In the application examples of the present invention, the time of the hydrodeoxygenation conversion reaction may be 30 min, 60 min, 90 min, 120 min or 150 min.

[0067] The catalyst provided by the present invention, its preparation method and application are described in detail below in conjunction with the embodiments, but they should not be construed as limiting the scope of protection of the present invention.

[0068] The preparation methods of the mesoporous silica described in Examples 1 to 4 and Comparative Examples 1 to 2 are:

[0069] Disperse 10 g of silicon source (silicon dioxide) in 180 mL of deionized water and stir at room temperature to obtain a silicon source aqueous solution;

[0070] 4 g of organosilane (dimethyloctadecyl[3-trimethoxysilylpropyl]ammonium chloride) was dissolved in 28 g of methanol and stirred vigorously (the stirring speed was 1500 rpm) to obtain a methanol solution of the organosilane;

[0071] 180 mL of the silicon source aqueous solution and 32 g of the methanol solution of the organosilane were mixed and poured into a three-necked flask, heated to 100° C., refluxed and stirred for 8 h, washed with ethanol, and vacuum dried at 90° C. for 16 h to obtain mesoporous silica.

[0072] Example 1

[0073] 0.6 g of nickel nitrate hexahydrate and 1.5 g of ammonium molybdate tetrahydrate were dissolved in 50 mL of deionized water, 1 g of the mesoporous silica was added, and the mixture was vigorously stirred at room temperature for 6 h (the stirring speed was 1500 rpm), 3 mL of ammonia water with a mass concentration of 28% was added dropwise until the pH value of the obtained mixed solution was 9, and the mixture was stirred at room temperature for 12 h, the precipitate was filtered out and centrifuged (the speed was 5000 rpm, and the time was 5 min), and the mixture was washed alternately with deionized water and ethanol for 3 times, and vacuum dried at 95° C. for 12 h to obtain a catalyst precursor;

[0074] The catalyst precursor was placed in a high-temperature tube furnace and reduced at 500° C. for 6 h in a hydrogen atmosphere, and then passivated at 30° C. for 1 h in a nitrogen atmosphere (nitrogen flow rate of 40 mL / min) to obtain a catalyst (nickel-molybdenum bimetallic loading of 20 wt %, nickel-molybdenum mass ratio of 1:1, average pore diameter of 14.8 nm, pore volume of 0.47 m 3 g -1 );

[0075] Figure 1 is the XRD diagram of the mesoporous silica (corresponding to SiO2 in the figure) and the catalyst (corresponding to Ni-Mo / SiO2 in the figure), Figure 1 It can be seen that the XRD spectrum of the catalyst only shows a broad and gentle peak of silica, which can be attributed to the presence of silica in an amorphous state, which has more lattice defects than crystalline materials, which helps to improve the dispersion of the loaded metal. After the introduction of nickel and molybdenum, the XRD spectrum did not change significantly, which may be related to the fact that the introduction of nickel and molybdenum did not cause significant damage to the carrier and the low loading amount;

[0076] Figure 2 The scanning electron microscope image and energy dispersion spectrum (a) of the mesoporous silica (corresponding to SiO2 in the figure) and the scanning electron microscope image and energy dispersion spectrum (b) of the catalyst (corresponding to Ni-Mo / SiO2 in the figure) and the element distribution diagram (c) of the catalyst are shown in FIG. Figure 2 It can be seen that the mesoporous silica presents a coral-like structure, and the Ni and Mo in the catalyst are uniformly loaded on the rough surface of the mesoporous silica, without obvious agglomeration of metal particles; the presence of O, Si, Ni and Mo elements can be seen from the energy dispersion spectrum, which is consistent with the XRD results. Among them, O and Si mainly come from the mesoporous silica, while Ni and Mo come from the active metal components introduced by the co-precipitation method;

[0077] Figure 3 is an X-ray photoelectron spectroscopy (XPS) diagram of the catalyst, wherein a is an XPS survey spectrum, b is a fitting curve of Ni 2p Ni-Mo / SiO2, and c is a fitting curve of Mo 3d Ni-Mo / SiO2; from a, it can be seen that O, Si, Ni, and Mo elements exist in the catalyst; from b, it can be seen that Ni 2P binding energy peaks are observed in the range of 848-884 eV, wherein Ni2P at 854.1 eV 3 / 2 The peak corresponds to the reduced Ni 0 , while Ni 2P near 874.4 eV 1 / 2 peak and Ni 2P at 856.7 eV 3 / 2 The peaks are attributed to the weak NiO interaction induced by the oxidation of the Ni nanoparticle surface, which indicates that the catalyst is easily oxidized in air. In addition, two peaks at 861.9 eV and 880.3 eV belonging to Ni 2+ Vibration satellite peaks. From c, we can see that the four obvious peaks at 229.2eV, 232.4eV, 235.1eV and 237.5eV are attributed to Mo 4+ and Mo 6+ , which means that Mo in the catalyst exists in multiple valence states;

[0078] Figure 4 are the N2 adsorption-desorption curves and pore size distribution diagrams of the mesoporous silica (corresponding to SiO2 in the figure) and the catalyst (corresponding to Ni-Mo / SiO2 in the figure), Figure 4It can be seen that according to the isotherm shape classified by the International Union of Pure and Applied Chemistry (IUPAC), the catalyst exhibits type I and type IV composite isotherms at a relative pressure of 0.8-1.0 MPa, and exhibits an obvious hysteresis loop. In addition, compared with silica, the catalyst exhibits a higher N2 adsorption capacity and obvious N2 condensation. From the perspective of pore size distribution, the catalyst has a larger pore volume and average pore size. The high pore volume can effectively prevent the catalyst from being deactivated due to carbon deposition, is more conducive to the interaction between the catalyst and the substrate, and improves accessibility to heavy molecules.

[0079] Example 2

[0080] 0.3 g of nickel nitrate hexahydrate and 0.8 g of ammonium molybdate tetrahydrate were dissolved in 50 mL of deionized water, 1 g of the mesoporous silica was added, and the mixture was vigorously stirred at room temperature for 6 h (the stirring speed was 1500 rpm), 3 mL of 28% ammonia water was added dropwise until the pH value of the obtained mixed solution was 9, and the mixture was stirred at room temperature for 12 h. The precipitate was filtered out and centrifuged (the speed was 5000 rpm for 5 min), washed with deionized water for 3 times, and dried at 95° C. overnight to obtain a catalyst precursor;

[0081] The catalyst precursor was placed in a high-temperature tube furnace and reduced at 500° C. for 6 h in a hydrogen atmosphere, and then passivated at 30° C. for 1 h in a nitrogen atmosphere (nitrogen flow rate of 40 mL / min) to obtain a catalyst (nickel-molybdenum bimetallic loading of 10 wt %, nickel-molybdenum mass ratio of 1:1, average pore diameter of 15.0 nm, pore volume of 0.50 m 3 g -1 ).

[0082] Example 3

[0083] 0.9 g of nickel nitrate hexahydrate and 2.5 g of ammonium molybdate tetrahydrate were dissolved in 50 mL of deionized water, 1 g of the mesoporous silica was added, and the mixture was vigorously stirred at room temperature for 6 h (the stirring speed was 1500 rpm), 3 mL of 28% ammonia water was added dropwise until the pH value of the obtained mixed solution was 9, and the mixture was stirred at room temperature for 12 h. The precipitate was filtered out and centrifuged (the speed was 5000 rpm for 5 min), washed with deionized water for 3 times, and dried at 95° C. overnight to obtain a catalyst precursor;

[0084] The catalyst precursor was placed in a high-temperature tube furnace and reduced at 500° C. for 6 h in a hydrogen atmosphere, and then passivated at 30° C. for 1 h in a nitrogen atmosphere (nitrogen flow rate of 40 mL / min) to obtain a catalyst (nickel-molybdenum bimetallic loading of 30 wt %, nickel-molybdenum mass ratio of 1:1, average pore diameter of 13.6 nm, pore volume of 0.46 m 3 ·g -1 ).

[0085] Example 4

[0086] 1.4 g of nickel nitrate hexahydrate and 3.1 g of ammonium molybdate tetrahydrate were dissolved in 50 mL of deionized water, 1 g of the mesoporous silica was added, and the mixture was vigorously stirred at room temperature for 6 h (the stirring speed was 1500 rpm), 3 mL of ammonia water with a mass concentration of 28 wt % was added dropwise until the pH value of the obtained mixed solution was 9, and the mixture was stirred at room temperature for 12 h, the precipitate was filtered out and centrifuged (the speed was 5000 rpm, the time was 5 min), and the mixture was washed with deionized water for 3 times, and dried at 95° C. overnight to obtain a catalyst precursor;

[0087] The catalyst precursor was placed in a high-temperature tube furnace and reduced at 500° C. for 6 h in a hydrogen atmosphere, and then passivated at 30° C. for 1 h in a nitrogen atmosphere (nitrogen flow rate of 40 mL / min) to obtain a catalyst (nickel-molybdenum bimetallic loading of 40 wt %, nickel-molybdenum mass ratio of 1:1, average pore diameter of 13.0 nm, pore volume of 0.41 m 3 ·g -1 ).

[0088] Comparative Example 1

[0089] 0.6 g of nickel nitrate hexahydrate was dissolved in 50 mL of deionized water, 1 g of the mesoporous silica was added, and the mixture was vigorously stirred at room temperature for 6 h (the stirring speed was 1500 rpm), 3 mL of ammonia water with a mass concentration of 28 wt % was added dropwise until the pH value of the obtained mixed solution was 9, and the mixture was stirred at room temperature for 12 h. The precipitate was filtered out and centrifuged (the speed was 5000 rpm for 5 min), washed with deionized water for 3 times, and dried at 95° C. overnight to obtain a catalyst precursor;

[0090] The catalyst precursor was placed in a high-temperature tube furnace and reduced at 500°C for 6 h in a hydrogen atmosphere, and then passivated at 30°C for 1 h in a nitrogen atmosphere (nitrogen flow rate of 40 mL / min) to obtain a catalyst (nickel loading of 10 wt%, average pore diameter of 13.7 nm, pore volume of 0.43 m 3 ·g -1 ).

[0091] Comparative Example 2

[0092] 1.5 g of ammonium molybdate tetrahydrate was dissolved in 50 mL of deionized water, 1 g of the mesoporous silica was added, and the mixture was vigorously stirred at room temperature for 6 h (the stirring speed was 1500 rpm), 3 mL of ammonia water with a mass concentration of 28 wt % was added dropwise until the pH value of the obtained mixed solution was 9, and the mixture was stirred at room temperature for 12 h. The precipitate was filtered out and centrifuged (the speed was 5000 rpm for 5 min), washed with deionized water for 3 times, and dried at 95° C. overnight to obtain a catalyst precursor;

[0093] The catalyst precursor was placed in a high-temperature tube furnace and reduced at 500°C for 6 h in a hydrogen atmosphere, and then passivated at 30°C for 1 h in a nitrogen atmosphere (nitrogen flow rate of 40 mL / min) to obtain a catalyst (molybdenum loading of 10 wt%, average pore diameter of 14.2 nm, pore volume of 0.44 m 3 ·g -1 ).

[0094] Application Example 1

[0095] 15 g of Salix psammophila raw material was placed in a 1000 mL high-pressure reactor, 200 mL of ethanol was added, the air in the reactor was replaced with N2 three times, and then 1 MPa of N2 was filled in, the reaction was carried out at 300°C for 2 hours, and the reaction mixture was cooled to room temperature; ethanol was used to thoroughly extract the reaction mixture to obtain ethanol soluble matter (light component), and the ethanol soluble matter was detected, analyzed and compared;

[0096] 3 g of the catalyst described in Example 1 and 15 g of the light component were placed in a 1000 mL autoclave, 200 mL of n-hexane was added, the air in the autoclave was replaced with N2 three times, and then 5 MPa of H2 was filled in, the reaction was carried out at 200° C. for 2 h, and the mixture was cooled to room temperature. The material components were analyzed by gas chromatography / mass spectrometry (GC / MS);

[0097] The light components were tested by GC / MS before and after hydrogenation. Figure 5 It is a comparison chart of the product components before (corresponding to the non-hydrogenation deoxygenation in the figure) and after (corresponding to the enhanced deoxygenation in the figure) hydrogenation of the light component. Figure 5 It can be seen that the yield of alcohol in the light component is greatly improved, and the relative content (relative content obtained by GC / MS analysis and integration) is increased from 3.5% to 49.8%, while the relative content of aromatic phenol (relative content obtained by GC / MS analysis and integration) is reduced from 51.7% to 16.8%. After the introduction of the catalyst, the main product changes from aromatic phenol before hydrogenation to cycloalkanol and alkane after hydrogenation. These changes mean that in the process of hydrodeoxygenation, heteroatom removal and saturation hydrogenation of aromatic rings are involved, which can be attributed to the synergistic effect of the bimetallic and the carrier (silicon dioxide). During the reaction, Ni can activate hydrogen and then saturate hydrogenate aromatic rings, while Mo plays a role in cracking the >CO-bridge bond, which is the key core of the conversion of guaiacol or 2-methoxycyclohexanol to cyclohexanol. This proves that the catalyst can effectively promote the hydrodeoxygenation of biomass-derived oil and achieve the purpose of obtaining higher-derived cycloalkanol.

[0098] Application Example 2

[0099] 0.5 g of guaiacol, 0.5 g of the catalysts described in Examples 1 to 4 and Comparative Examples 1 to 2, and 200 mL of n-hexane were placed in a 1000 mL stainless steel autoclave, purged with N2 for 3 times, pressurized with 5 MPa of H2 at room temperature, and kept at 200°C for 120 min. The autoclave was cooled to room temperature and the reaction mixture was taken out and filtered. The obtained filtrate was analyzed by GC / MS. The results of the catalysts described in Examples 1 to 4 and Comparative Examples 1 to 2 for the hydrodeoxygenation conversion of guaiacol are shown in Table 1:

[0100] Table 1 Results of the hydrodeoxygenation conversion of guaiacol using the catalysts described in Examples 1 to 4 and Comparative Examples 1 to 2

[0101]

[0102] As shown in Table 1, under the same conditions, the main products of the hydrodeoxygenated guaiacol by the catalysts described in Examples 1 to 4 and Comparative Examples 1 to 2 are cycloalkanols, especially cyclohexanol. The catalytic effect of the catalysts described in Examples 1 to 4 is much better than the catalytic performance of the catalysts described in Comparative Examples 1 to 2, and the main product yield of the catalyst described in Example 1 is the highest (the yield of cyclohexanol is 50.1 mol%). On the basis of the above, with the increase of the loading of nickel and molybdenum, the yield of the main product does not increase, but the yield of cycloalkanes decreases. This is because the increase of the loading of Ni and Mo strengthens the ability of the catalyst to crack the >CO-bridge bond, which is not conducive to the formation of alcohol compounds. Therefore, the catalyst described in Example 1 is most conducive to the acquisition of alcohol compounds.

[0103] Application Examples 3 to 15

[0104] Referring to Application Example 2, the difference lies in the pressure of H2 pressurization and the insulation temperature and time after pressurization. The specific differences and results of the catalysts described in Examples 1 to 4 and Comparative Examples 1 to 2 for the hydrodeoxygenation conversion of guaiacol are shown in Table 2.

[0105] Table 2 Catalytic conditions and results of the catalysts described in Examples 1 to 4 and Comparative Examples 1 to 2 for the hydrodeoxygenation conversion of guaiacol

[0106]

[0107]

[0108] As shown in Table 2, temperature is crucial for hydrodeoxygenation conversion. As the temperature increases, the conversion rate of guaiacol increases accordingly, and the conversion rate reaches 100% at 200°C, and the main product cyclohexanol yield also reaches the highest (50.1mol%) at 200°C. However, the yield of the main product does not continue to increase when the temperature continues to increase, but deoxygenates to generate cyclohexane. This change shows that high temperature is conducive to removing heteroatoms but not conducive to hydrogenation, so 200°C is the best temperature for obtaining cycloalkanol. At 200°C, as the initial hydrogen pressure increases, the yield of the main product increases monotonically, but considering the economic usability, it is appropriate to adopt 5MPa. In addition, at 200°C and 5MPa initial hydrogen pressure, as time increases, the conversion rate of guaiacol and the yield of the main product cyclohexanol continue to increase, and reach the highest at 120min, but further extending the time does not increase the yield of the main product, in other words, the yield of the main product will tend to be stable. Therefore, 200 °C, 5 MPa initial hydrogen pressure and 120 min are the optimal conditions for the conversion of guaiacol to cycloalkanol. At this time, the aromatic ring is not only completely hydrogenated, but also the specific functional groups can be retained. This series of changes can be attributed to the fact that the active hydrogen species formed by H2 activation on the catalyst prepared by the coprecipitation method plays a vital role in the acquisition of derived cycloalkanols. First, the catalyst can promote the activation of H2 to generate diatomic active hydrogen and H + , diatomic active hydrogen and H + The coordinated transfer of guaiacol promotes the conversion of guaiacol to derived cycloalkanol. Therefore, the catalyst of the present invention has high catalytic activity and high cycloalkanol selectivity.

[0109] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A catalyst, characterized in that The invention comprises organosilane-modified mesoporous silica and nickel-molybdenum bimetal supported on the organosilane-modified mesoporous silica.

2. The catalyst according to claim 1, characterized in that The loading amount of the nickel-molybdenum bimetal in the organosilane-modified mesoporous silica is 10 wt % to 40 wt %.

3. The catalyst according to claim 1 or 2, characterized in that The mass ratio of nickel to molybdenum in the nickel-molybdenum bimetal is 1:(1-4).

4. The method for preparing the catalyst according to any one of claims 1 to 3, characterized in that: The following steps are involved: After mixing organosilane-modified mesoporous silica, soluble molybdenum salt, soluble nickel salt and water, ammonia water is added dropwise to perform a coprecipitation reaction to obtain a catalyst precursor; The catalyst precursor is calcined in a reducing atmosphere to obtain the catalyst.

5. The preparation method according to claim 4, characterized in that: The soluble molybdenum salt is ammonium molybdate tetrahydrate and / or ammonium heptamolybdate; The soluble nickel salt is nickel nitrate hexahydrate and / or nickel sulfate heptahydrate; The mass concentration of the ammonia water is 25-28%.

6. The preparation method according to claim 5, characterized in that: The mass ratio of the organosilane-modified mesoporous silica to the soluble molybdenum salt is 1:(0.5-4); The mass ratio of the organosilane-modified mesoporous silica to the soluble nickel salt is 1:(0.3-1.5); The usage ratio of the organosilane-modified mesoporous silica and ammonia water is 1 g: (1-5) mL; The usage ratio of the organosilane-modified mesoporous silica to water is 1 g: (10-60) mL.

7. The preparation method according to claim 4, characterized in that: The calcination temperature is 400-550° C. and the calcination time is 4-8 hours.

8. The preparation method according to claim 4, characterized in that: The preparation method of the organosilane-modified mesoporous silica comprises the following steps: The silicon source aqueous solution and the methanol solution of the organosilane are mixed, and then refluxed, stirred, washed and dried in sequence to obtain the organosilane-modified mesoporous silica.

9. The preparation method according to claim 8, characterized in that: The silicon source in the silicon source aqueous solution includes silicon dioxide and / or sodium silicate; The organosilane in the methanol solution of organosilane includes dimethyloctadecyl[3-trimethoxysilylpropyl]ammonium chloride and / or dimethyloctadecyl[3-ethoxysilylpropyl]ammonium chloride.

10. Use of the catalyst according to any one of claims 1 to 3 or the catalyst prepared by the preparation method according to any one of claims 4 to 9 in the hydrodeoxygenation conversion reaction of biomass-derived bio-oil.

Citation Information

Cited By

  • Ni-molybdenum oxide / Nb2O5 nano composite catalyst as well as preparation method and application thereof

    CN120679551A